Perbedaan Tingkat Kekerasan Dan Daya Terima Biskuit DariTepung Sorgum Yang Disosoh Dan Tidak Disosoh - Rosniar, Mariza; , Eni Purwani, S.Si., M.Si; , Rusdin Rauf, STP., MP (2016)
Background : Since develop diversification program, Indonesia needs to develop various types of plants that potentially support food security such as sorghum. Sorghum has potential used as flour to make biscuits through the milling process. Milling of sorghum will affect the physicochemical and organoleptic properties of food. Purpose : The purpose of this study was to determine the differences of hardness level and accpetability biscuit with milled and whole sorghum flour. Method : The completely randomized design with 6 different substitution of milled and whole sorghum namely 0%, 15%, and 30% was used in this study. The hardness and acceptability of biscuits was analyzed by t test and Anova One Way. If there was any significancy, it continued with Duncan test. Result : The results showed that hardness of biscuits by different types of sorghum flour at 0%, 15%, and 30% had a value of p> 0.05. Effect of substitution of milled sorghum flour to the hardness has a value of p = 0.002. Substitution effect of whole sorghum flour for the hardness has a value of p = 0.164. Acceptability biscuits of substitution milled and whole sorghum average of p<0,05. Conclusion : There was substitution effect of milled sorghum flour for the hardness level. Moreover, there was substitution effect of sorghum flour in acceptability of biscuits include color, flavour, taste, texture, and overall. However, there was no differencess of hardness level based on the type of sorghum, also there was no interaction between types of sorghum flour with the different substitution. Suggestion : Based on the highest acceptability, suggested to substitute15% milled sorghum flour in biscuit.